Answer: To find the ten terms of the sequence Tn=n^2–3n-4 Plug in the values of n=1,2,3.. upto 10 to get the ten terms When n=1,T1=(1)^2–3*1–4=1–3–4=—6 When n=2,T2=(2)^2–3*2–4=4–6–4=—6 When n=3,T3=(3)^2–3*3–4=9–9–4=—4 When n=4,T4=(4)^2–3*4–4=16–12–4=0 When n=5,T5=(5)^2–3*5–4=25–15–4=6 When n=6,T6=(6)^2–3*6–4=36–18–4=14 When n=7,T7=7^2–3*7–4=49–21–4=24 When n=8,T8=8^2–3*8–4=64–24–4=36 When n=9,T9=9^2–3*9–4=81–27–4=50 When n=10,T10=10^2–3*10–4=100–30–4=66 The ten terms are,—6,—6,—4,0,6,14,25,36,50,66 Step-by-step explanation: same Method Reply

Answer:To find the ten terms of the sequence

Tn=n^2–3n-4

Plug in the values of n=1,2,3.. upto 10 to get the ten terms

When n=1,T1=(1)^2–3*1–4=1–3–4=—6

When n=2,T2=(2)^2–3*2–4=4–6–4=—6

When n=3,T3=(3)^2–3*3–4=9–9–4=—4

When n=4,T4=(4)^2–3*4–4=16–12–4=0

When n=5,T5=(5)^2–3*5–4=25–15–4=6

When n=6,T6=(6)^2–3*6–4=36–18–4=14

When n=7,T7=7^2–3*7–4=49–21–4=24

When n=8,T8=8^2–3*8–4=64–24–4=36

When n=9,T9=9^2–3*9–4=81–27–4=50

When n=10,T10=10^2–3*10–4=100–30–4=66

The ten terms are,—6,—6,—4,0,6,14,25,36,50,66

Step-by-step explanation:same Method